Committed to us: Predicting relationship closeness following nonmarital romantic relationship breakup. (June 2015) - Tan, Kenneth; Agnew, Christopher R.; VanderDrift, Laura E.; Harvey, S. Marie
There is little research on the nature of relationships between individuals following the termination of a nonmarital romantic relationship. It is largely unknown to what extent former romantic partners remain close following breakup. The present research used the Investment Model of Commitment Processes, assessed prior to romantic breakup, to examine the closeness of post-breakup relationships. Results obtained from two waves of data collected from 143 young adults involved in romantic relationships at Time 1 and experiencing a romantic breakup by Time 2 indicated that pre-breakup romantic commitment mediated the effects of pre-breakup romantic satisfaction, investments, and alternatives on post-breakup closeness, with higher pre-breakup commitment predicting greater post-breakup closeness. Implications of these findings for understanding the underlying dynamics of ongoing interpersonal relationships and directions for future research are discussed.